POLICY FOR THE DEVELOPMENT OF CULTIVATED FISHERY COMMERCE IN THE PROVINCE OF THE BANGKA BELITUNG ISLANDS - Endang Bidayani; Tiara Puspa Anjani; Muhammad Fachri (Jurusan Akuakultur, Universitas Bangka Belitung, 2023)
The trading system for aquaculture products is the process of distributing goods in the form of fish or derivative products from producers to final consumers effectively and efficiently. The objectives of this research are: 1) Analyzing aquaculture supply chain management in the Bangka Belitung Islands Province; and 2) Develop recommendations for the direction of development of the aquaculture trade system. This research method is a survey. The data sources in this research are primary and secondary data. The primary data collection method is qualitative, namely the researcher makes questionnaires, observations and interviews. Secondary data comes from production data from the Fisheries Service/BPS/pokdakan/regency/city companies in the Bangka Belitung Islands Province. Respondents in this study were informants at the District/City Fisheries Service, Pokdakan, and the shrimp farming industry (micro/small/medium/large scale). Data analysis is descriptive. The research results show that the grouper aquaculture supply chain is more efficient than the shrimp aquaculture supply chain, because it involves more companies from outside the Bangka Belitung Islands Province. The direction of development of the aquaculture trade system which refers to supply chain management has not yet implemented Minister of Maritime Affairs and Fisheries Regulation No. 5/Permen-KP/2014 concerning the National Fish Logistics System (SLIN). Understanding of the cold chain is still low. Then the problem at the collection and storage stage is the availability of facilities (cold storage) as well as the availability of basic infrastructure such as electricity, clean water and others, and the availability of facilities (unplug reefer).